Repellent Activity Of N-Hexane Extract From Ocimum basilicum Leaves And Stem Against Aedes aegypti - Indri Ramayanti; Ratika Febriyani; Annisa Nurul Jannah (Buletin Farmatera, 2020)
Aedes aegypti is known to be a major vector for dengue hemorrhagic fever. Vector control involves repellent usage. Synthetic repellent is known to be corrosive and natural repellent might be safer and more environmentally friendly. Ocimum basilicumstem and leaves contains essential oil with bioactivity against Aedes aegypti. This research aims to analyze the bioactivity of repellent from Ocimum basilicum n-hexane extract and demonstrate the effective concentration (EC90) against Aedes aegypti. This research was designed as experimental complete random design research. Aedes aegypti was supplied by Laboratorium Entomologi, Lokalitbang P2B2, Baturaja, South Sumatra. The repellent activity was tested according to repellent test guideline and Standardized Household Pesticide Efficacy Test Protocol (Metode Standar Pengujian Efikasi Pestisida Rumah Tangga). Every extract was diluted to 15%, 25%, and 35% using 96% ethanol and applied to black cloth that was fixed against the wall of test cage. Negative control was provided using 96% ethanol and positive control was achieved with 13% DEET (brand X repellent). Repellent activity was analyzed using one-way ANOVA and Probit test. EC90 was achieved at 45.13%. N-hexaneextract from basil stem and leaves therefore proven as effective against Aedes aegypti.